Prevention and consequences of job burnout - Einarsdóttir, Arney; Ólafsdóttir, Katrín; Gunnarsdóttir, Sigrún (Research in applied business and economics, 2023)
The discussion on job burnout and increased work demands in the workplace has increased greatly in recent years in Iceland, as well as abroad. Research has mainly focused on occupations and professions where employees work with people, and burnout is often associated with job stress that has not been successfully managed. Job burnout is not limited to those jobs, and the attention could be directed to the positive work-related attitudes of employees and the expected consequences in the attitudes and behavior of employees at work. This paper aims to shed light on the attitude- and experience-related factors that can prevent employees from job burnout and the emotional and behavioral consequences of burnout symptoms, among employees in various occupations and professions in Iceland. Maslach Burnout Inventory General Survey was used to measure emotional exhaustion. Data was collected electronically among 898 employees in different jobs and occupations in a total of 32 organizations in the fall of 2019 for a response rate of 47%. The results show a negative correlation between job satisfaction, perception of fairness, and trust, with burnout, which indicates that job satisfaction, perceived fairness, and trust in the workplace can have protective effects on burnout symptoms. Furthermore, the results show a negative correlation between burnout symptoms and employee commitment to work, and a positive correlation between burnout symptoms and intentions to quit. The results of this study provide insight into the relationship between positive attitudes of employees with burnout and possible negative effects on organizations as a consequence. The results contribute to knowledge about burnout among employees in various occupations in Iceland. Results should also be useful to managers and those working in the field of HRM in their targeted efforts to reduce or minimize burnout at work. Umræða um kulnun og aukið álag í starfsumhverfi fólks hefur aukist mjög hérlendis síðustu ár eins og víða erlendis. Í rannsóknum hefur ...